Ohmic heating as an alternative food processing technology - Anderson, Destinee R (Kansas State University, 2008)
Ohmic heating for the food industry consists of using electrical energy to heat foods as a method of preservation, which can in turn be used for microbial inactivation or several other processes such as pasteurization, extraction, dehydration, blanching or thawing. Few studies have been conducted on the usefulness of this environmentally friendly processing technique. Due to the lack of sufficient information on research into ohmic heating for the food industry, a few of the published studies are discussed here in detail. This report also focuses on self-conducted research using ohmic heating to determine its effect on Lactobacillus acidophilus inactivation versus conventional heating. Lactobacillus acidophilus was inoculated into MRS broth and incubated for 24 hours. The sample was then inoculated into sterile buffer at a dilution rate of 1:100. Samples of the diluted culture were subjected to either low voltage (18 V) or conventional heating (300°C) over a hotplate stirrer. Temperature was monitored on test and control samples to achieve an endpoint of 90°C. Samples were taken at regular intervals, plated onto MRS agar and incubated for 72 hours at 35°C to compare plate count expressed as colony forming units per milliliter (cfu/mL). Temperature was uniform throughout the ohmically heated sample and reached the endpoint more quickly than the conventionally heated sample, which also had cold spots. The total plate count at the end of the experiment was less for the ohmically heated sample versus the conventionally heated sample. Ohmic heating was more effective in inactivation of Lactobacillus acidophilus than conventional heating, most likely due to the more rapid and uniform heating of the sample, and possible electroporation of the cells.
Keywords: ohmic heating; food processing techniques; Agriculture, Food Science and Technology (0359)